Use of autogenous fascia lata graft in the treatment of chronic segmental defect of the common calcaneus tendon in domestic feline - Tertuliano Marinho, Paulo Vinicius; Zani, Carolina Camargo; de Oliveira, Suelton Lacerda; Feitosa, Caroline Cezaretti; Minto, Bruno Watanabe [UNESP] (My University, 2018)
Background: The common calcaneus tendon is formed by the common tendon of the femoral biceps muscle, tendon of the superficial digital flexor muscle and gastrocnemius muscle tendon, and its rupture is related to acute traumas in small animals. Among some applications described, surgical repair can be adopted in the correction of tendon ruptures and the use of grafts may be indicated in some severe lesions, where it is not possible to perform tenorrhaphy. This study aims to report the case of a feline with rupture of the common calcaneus tendon in which the tenorrafia associated with the autogenous fascia lata graft was performed as adjuvant to the cicatrization of the same. Case: A 24-month-old, undefined male feline with approximately 3 kg was treated at the FCAV Veterinary Hospital, UNESP Jaboticabal, State of São Paulo, Brazil, with a history of falling, for approximately two weeks, and has since plantigrade posture. Upon physical examination, it was possible to identify a discontinuity of the common calcaneus tendon. The radiographs were performed, which did not show any bone changes. A hemogram and biochemical profile were performed, which were within normal limits. The patient underwent surgery, and a complete lesion of the common calcaneus tendon was identified, with a chronic aspect. Approximation of the stumps was impossible, so a flap of fascia lata, about two centimeters long and one centimeter wide, was removed, which was used as a bed and tendon support for tendon growth. After removal all of the present fibrosis, the tendon stumps were approximated by means of modified Kessler suture with mononylon thread, and fascia lata flap of the ipsilateral limb was sutured with separate single points in both tendon ends and in their lateral and medial portion. In the tibiotarsic joint, the external skeletal fixator type II was used for immobilization, during a period of 30 days. In the immediate postoperative period the patient was already able to support the member on the floor, with progressive improvement, and after 60 days of surgery the animal presented complete support of the limb, without pain or any other alteration coming from the surgery. The animal presented a rapid recovery after surgical treatment with the autogenous fascia lata flap. Discussion: The rupture of the common calcaneus tendon is not commonly reported in felines and its occurrence is related to acute trauma, where the animals will present lameness and plantigrade posture. Depending on the degree of tendon involvement, there are different procedures that may be indicated, such as tenorrhaphy, reimplantation for avulsion cases, and transplantation with grafts when there is segment loss. In the present study, the use of tenorrhaphy associated with the implantation of autogenous lata-fascia graft was chosen, since the grafts generally provide the framework for healing due to its replacement by collagen tissue in the recipient, in addition to providing mechanical protection initially. Fascia lata, due to its antigenic character as being autogenous, has been shown to be a viable and easily obtained surgical option. The use of the fascia lata graft associated with external immobilization with external fixator type II in the tibiotarsal joint allowed an excellent result and is therefore a recommended treatment for cases of rupture of the common calcaneus tendon in felines.
Uso de enxerto autógeno de fáscia lata no tratamento de defeito segmentar crônico do tendão calcâneo comum em felino doméstico
Keywords: Cats; Lameness; Plantigrade stance